WOMEN ENTREPRENEURSHIP IN SMES: A SYSTEMATIC REVIEW OF DIGITAL INNOVATION, GENDER EQUALITY, AND SUSTAINABLE GROWTH STRATEGIES - Asrijal Bintang; Ismail Rasulong; Kahar (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This systematic literature review explores the interconnected dimensions of digital innovation, gender equality, and sustainability in women-owned small and medium-sized enterprises (SMEs). The primary aim is to synthesize existing knowledge to address integration challenges these enterprises face. The researchers analyzed 436 peer-reviewed articles from the Scopus database, published between 2010 and 2025, using bibliometric and qualitative thematic techniques based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. Findings highlight that digital innovation significantly enhances market access, operational efficiency, and resource mobilization, empowering women entrepreneurs to overcome structural barriers. Gender equality initiatives play a crucial role in creating supportive ecosystems, promoting diverse leadership styles, and fostering inclusive organizational cultures conducive to sustainable business practices. Thematic analyses reveal specific success factors including robust social networks, targeted mentorship programs, and inclusive financial mechanisms. However, systemic barriers persist, notably limited access to capital, entrenched sociocultural biases, and insufficient digital literacy. Methodologically, research predominantly utilizes quantitative approaches, suggesting a need for integrated mixed-method frameworks to better capture nuanced entrepreneurial experiences. Geographical disparities indicate that women entrepreneurs face different challenges and opportunities across developed and developing contexts, underscoring the necessity for context-specific policy interventions. This review adds to our understanding by combining ideas from entrepreneurial ecosystem perspectives, Gender Empowerment Theories, and the Resource-Based View, providing a complete look at sustainable, fair, and digitally innovative business practices. Future research should focus on intersectional methodologies, longitudinal studies, and comparative analyses across diverse contexts.